KEAP1‐NRF2/HO‐1 Pathway Promotes Ferroptosis and Neuronal Injury in Schizophrenia - Feng Zhu; Tangqun Dan; Shuguang Hua (Brain and Behavior)
ABSTRACT Background This study investigates the role of the KEAP1‐NRF2/HO‐1 signaling pathway in inducing ferroptosis and contributing to neuronal damage in schizophrenia. Methods We retrieved schizophrenia‐related data and ferroptosis‐related genes from the RNA microarray dataset GSE27383 and FerrDB database, respectively. Bioinformatics data identified KEAP1 as a downregulated gene, which was validated using qRT‐PCR and Western blot. We assessed intracellular Fe2⁺ content, MDA levels, GSH, and GPX4 in the prefrontal cortex and peripheral blood mononuclear cells (PBMCs) of patients with schizophrenia. Cortical interneurons (cINs) were generated from human‐induced pluripotent stem cells (hiPSCs) of patients with schizophrenia and used to explore KEAP1 alterations during neurodevelopment. In addition, KEAP1 overexpression was induced in cINs via transfection with pcDNA KEAP1. The intracellular Fe⁺ levels, oxidative stress indicators, lipid peroxidation, and inflammatory cytokines were measured after transfection. To investigate molecular mechanisms, KI696—a high‐affinity probe that disrupts the KEAP1–NRF2 interaction—was applied, and changes in oxidative stress, lipid peroxidation (C11‐BODIPY staining), iron metabolism, and inflammatory pathways were evaluated. Results Patients with schizophrenia exhibited underexpression of KEAP1, a key regulator of ferroptosis, along with elevated intracellular Fe2⁺ levels and increased MDA concentrations, indicating enhanced lipid peroxidation and oxidative stress. Reduced GPX4 activity and GSH levels were also observed, suggesting an increased susceptibility to ferroptosis. To further explore this, cINs derived from hiPSCs of patients with schizophrenia were studied. These cells showed decreased KEAP1 expression. Overexpression of KEAP1 in cINs led to a reduction in intracellular Fe2⁺ concentrations and oxidative damage, highlighting KEAP1's regulatory role in ferroptosis. In addition, treatment with KI696 induced significant alterations in pathways related to oxidative stress, iron metabolism, antioxidant defenses, and inflammation. Conclusion Our findings indicate that the KEAP1‐NRF2/HO‐1 pathway contributes to ferroptosis and neuronal injury in schizophrenia.